1 PENGARUH LATIHAN HORIZONTAL SWING TERHADAP HASIL PUKULAN PADA ATLET PELATDA SOFTBALL PUTRI RIAU - Ridho Nofebri Yanto; Slamet ' '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study aims to improve basic movements of dance arts and cultural offerings in the learning and skills of fourth grade at SDN 19 prairie flat through the application of training methods. Subjects in this study were fourth grade students of SDN 19 school year 2011/2012 the number of students as many as 34 people. While the object of this study is to improve basic motor skills through the application of methods of dance training offerings. The research was conducted in two cycles, the first cycle consisted of two meetings with the end of the cycle and replicates as well as on the second cycle. Data collection instrument in this study is the observation sheet teacher, student observation sheet, sheet assessment process and outcomes assessment sheets. Percentage of students' ability level before action was 1223 with the average category 35.97, less capable. At UAS I rose to the level of student ability 2065 with an average of 60.73, the categories are quite capable. While the level of basic motor skills of dance offerings after the action (UAS II) was 2715 with an average of 79.85, the category can afford. Improved basic motor skills of students before the dance offerings until after the action 44.06. Data collection using instruments and teacher observation sheet observation sheets students, percentage of student learning activities in the first cycle and the first meeting of the second cycle 40.62% 93.65% second meeting increased 52.39%, next activity of teachers in the first cycle and the first meeting of the second cycle of 75% 97. increased 22.22%. From the above it shows that through the application of training methods to improve basic motor skills of dance arts and cultural offerings in the learning and skills of fourth grade at SDN 19 Padang Datar Kecamatan Tanjung Emas Sumatera Barat.Keywords: Method Drill, Dance Basic Motion Capability Offerings